PADRONIZACAO E CARACTERIZAÇÃO DE BIOMEMBRANA INCORPORADA COM EXTRATO DE Chenopodium ambrosioides L. (Mastruz) ASSOCIADO AO EXTRATO PADRONIZADO DE PRÓPOLIS DE Apis melifera (EPP-AF®) - ROCHA, Marla Raquel Pontes da (2022)
The production of biomembranes as biodressings has been the object of interest of the pharmaceutical industry due to their healing and antiseptic effects, mainly in the treatment of chronic wounds that have a great socioeconomic impact. The use of natural products incorporated into biomembranes has lately been investigated for their biological potential and the possibility of slow release. Our research group has studied Chenopodium ambrosioides and the standardized extract of Apis mellifera propolis (EPP-AF®) in the treatment of inflammation and wounds. Thus, the aim of this work was to produce, characterize and test in vitro antimicrobial and wound healing activities biomembranes incorporated with C. ambrosioides (Mastruz) leaf extract associated or not with EPP-AF® for potential use as a biodressing. For this purpose, the methods employed were categorized into in vitro tests of biological activity (cytotoxicity test of extracts; antisepsis and healing tests of biomembranes) and physicochemical analyzes (macroscopic characterization of biomembranes; infrared spectroscopy by Fourier transform ( FT-IR); thermal analysis by thermogravimetry (TG)). Biodressings were obtained with bacterial cellulose biomembranes incorporated into: C. ambrosioides extract (0.05 mg/mL) - G1 ao ; EPP-AF® (0.024 mg/mL) G2 – with and to the extract of C. ambrosioides associated with EPP-AF® (0.074 mg/mL) - G3. Biodressing G1 did not show antibacterial activity, while biodressing G2 and G3 showed antibacterial activity against S. aureus ATCC 25923; In in vitro healing assays, fibroblasts showed better adhesion to G1 biomembrane than to G2 biomembrane; The MTT cytotoxicity assays were carried out in fibroblasts, considering the extracts of C. ambrosioides, EPP-AF® and their associations, being then, the cellular proliferation observed in the concentrations between 7 and 1000 µg/mL. The data allow us to conclude that the biobandages composed of biomembranes with mastruz extracts and EPP-AF®, have the potential to integrate the third generation of biobandages in wide development, since this association favored their main therapeutic effects, such as healing and antibacterial on a common target, that is, it is a biomaterial of high biological compatibility, with aspects of reproducibility combined with biofunctionality costs, as these criteria constitute the greatest concern in the production process of the industrial sector, and especially in products aimed at health.